2006
DOI: 10.1088/0952-4746/26/1/006
|View full text |Cite
|
Sign up to set email alerts
|

Thermal neutron fluence measurement in a research reactor using thermoluminescence dosimeter TLD-600

Abstract: A thermal neutron fluence in the range between 10(11) and 10(13) n cm(-2) in the reactor core of the Tehran research reactor has been measured using TLD-600 thermoluminescence dosimeters. After a thermal treatment of 1 h at 400 degrees C followed by 20 h cooling down to room temperature of pre-exposed dosimeters in the reactor, the accumulated TL light was measured after periods of storage of 24, 48 and 72 h. The influence of the irradiation-induced damage effect on the response of TLDs and their subsequent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…For example Yang et al [14] have suggested the use of CaSO 4 : Dy TL pellets embedded with a 6 Li compound for a thermal neutron measurement. Torkzadeh and Manouchehri [15] have measured the thermal neutron fluence in a research reactor using TLD-600. Pradhan and Bhatt [16] have studied the thermoluminescence response of LiF(Mg, Cu, P) and LiF TLD-100 to Thermal Neutrons, 241 Am Alphas and Gamma Rays.…”
Section: Introductionmentioning
confidence: 99%
“…For example Yang et al [14] have suggested the use of CaSO 4 : Dy TL pellets embedded with a 6 Li compound for a thermal neutron measurement. Torkzadeh and Manouchehri [15] have measured the thermal neutron fluence in a research reactor using TLD-600. Pradhan and Bhatt [16] have studied the thermoluminescence response of LiF(Mg, Cu, P) and LiF TLD-100 to Thermal Neutrons, 241 Am Alphas and Gamma Rays.…”
Section: Introductionmentioning
confidence: 99%